Changes in attitudes, risky practices, and HIV and syphilis prevalence among female sex workers in Brazil from 2009 to 2016. (May 2018) - Szwarcwald, Célia Landmann; de Almeida, Wanessa da Silva; Damacena, Giseli Nogueira; de Souza-Júnior, Paulo Roberto Borges; Ferreira-Júnior, Orlando da Costa; Guimarães, Mark Drew Crosland
Abstract: Background: The present study aims at investigating the progress made toward controlling the human immunodeficiency virus (HIV)/AIDS epidemic among female sex workers (FSW) from 2009 to 2016. Methods: The baseline of respondent-driven sampling (RDS) study among FSW was carried out in 2009, in 10 Brazilian municipalities. In 2016, information on FSW were collected in 12 municipalities. The analyses took into account the dependence among observations, resulting from the recruitment chains, and the unequal probabilities of selection, resulting from the different network sizes. We analyzed changes in attitudes and risky behavior practices as well as variations in HIV and syphilis prevalence based on the comparison of 95% confidence intervals for each estimate. Results: Information on 2523 (2009) and 4245 (2016) FSW were analyzed. Commercial sex debut shifted to younger ages: while in 2009 the proportion of women who started sex work under 18 years old was 28.3%, in 2016 this percentage rose to 38.3%. The proportion of FSW affiliated to a nongovernmental organization (NGO) in defense of their rights (14.0%), in 2009, decreased to 7.8%, in 2016, as well as the proportion of FSW who received counseling on sexually transmitted infections (STI) in the past 6 months, from 47.5% to 24.4%. Relevant improvements were found for HIV testing in the last 12 months (from 20.3% to 39.3%). The proportions of those who were never tested for syphilis dropped from 57.9% to 48.5%. However, an opposite decreasing trend was found for the Pap smear examination in the last 12 months, decreasing from 43.6% to 31.5%. Regular condom use with clients significantly increased in the period. Regarding HIV prevalence, the 5% level was sustained and no significant differences were found, but syphilis prevalence was found to be more than 3 times higher in 2016 (8.5%) than in 2009 (2.4%). Discussion: Many are the challenges to be faced in attempting to reverse the upward trend of syphilis among FSW in Brazil. Despite the progress in condom distribution free of charge, it is necessary to increase awareness campaigns, emphasize the use, reaffirm STI counseling, and reiterate the need of regular syphilis screening in this key population group.